Lithium Recovery from Spent Li-Ion Batteries Using Combination of Organic Acid: Leaching and Precipitation Studies - Asful Hariyadi; Dwi Rosa Maharani; Mutia Reza (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The demand for lithium-ion batteries (LiBs) is increasing significantly leading to supply shortages for metals, such as lithium. In this study, leaching combination of citric acid along with ascorbic acid, and precipitation of lithium with sodium carbonates were used to recover lithium as lithium carbonate. The effect of acid concentration and precipitating agent were analyzed, then the leaching and precipitation conditions will also be further analyzed to optimize the final product. The results show that leaching with citric acid 1 M and ascorbic acid 0.5 M, solid liquid ratio is 35 g/L, the reaction temperature 80°C, and reaction time 3 h, can attain lithium recovery up to 91%. As well as the best condition to precipitate lithium is at pH 12, reaction temperature 100°C, and the [CO32-]/[Li+] mol ratio was 0.75 mol/mol with recovery of lithium up to 92%. The X-Ray Diffraction results from the final product are further confirmed that most of the product is composed of lithium carbonate. In addition, FTIR results indicate that the absorption spectrum that is formed shows that there is a C = O bond that matches the characteristics of the carbonate peak.